"Celtic migrations": Fact or fiction? Strontium and oxygen isotope analysis of the Czech cemeteries of Radovesice and Kutná Hora in Bohemia. Issue 4 (18th August 2014) - Scheeres, Mirjam; Knipper, Corina; Hauschild, Maya; Schönfelder, Martin; Siebel, Wolfgang; Pare, Christopher; Alt, Kurt W.
ABSTRACT Strontium and oxygen isotope analysis of human remains from the early La Tène (fourth/third century BC) Czech cemeteries of Radovesice I (RAD I), Radovesice II (RAD II), and Kutná Hora were conducted to investigate the importance of residential changes during the period of the historic "Celtic migrations". In the initial phases (LT A/B), the grave goods of these cemeteries are typical for the core area of the La Tène culture, while around 300 BC (LT B2) an alteration occurs and typical Bohemian styles arise, and connections to Moravia and the Danubian region become visible. The strontium isotope ratios are highly varied with 87Sr/86Sr values between 0.7062 and 0.7153 in Radovesice, and between 0.7082 and 0.7147 in Kutná Hora. The oxygen isotope data are more homogeneous and yield δ18Op ratios from 14.8‰ to 17.2‰ [mean: 16.2‰ ± 0.5 (1σ)] in Radovesice, and from 14.9‰ to 17.3‰ [mean: 16.5‰ ± 0.6 (1σ)] in Kutná Hora. Because the geological properties of the landscapes around the sites are variable and complex, most of the observed variations among the strontium isotope ratios may have been caused by agricultural practices, such as regularly changing farming land. Nevertheless, there are some individuals who differ completely from the regional isotopic baseline values. This suggests that at least a small part of the community migrated, which does not seem to be correlated with any particular phase of the La Tène period. Remarkably, it is mainly males who seem to be of nonlocal origin, and particularly those who were buried as warriors. Females, on the other hand, appear to have been more closely bonded to the Bohemian region. Whether the "foreign" individuals with differing isotopic compositions came from Moravia or the Danubian region remains debatable. Am J Phys Anthropol 155:496–512, 2014. © 2014 Wiley Periodicals, Inc.